Explaining variation in the intrusiveness of regional human rights remedies in domestic orders - Cali, Basak (Icon-International Journal of Constitutional Law, 2018)
Regional human rights systems vary with respect to the intrusiveness of human rights remedies into the domestic orders of states from a spectrum of more intrusive remedies in the Americas to less intrusive remedies in Europe. This article identifies three potential explanations as to why the intrusiveness of human rights remedies varies across the three regional systems: (i) the legal design explanation, (ii) the case-history explanation, and (iii) the legal culture explanation. The article argues that of these competing explanations, the legal culture explanation fares better than the other contenders in accounting for variation in the intrusiveness of remedies over time. The other two explanations, however, are also of use. The legal design explanation accounts for why the courts in the Americas and Africa are more amenable to intrusive remedies. The case-history explanation is able to explain sudden bursts of intrusive remedies in all three regions.
CRIS-Team Scopus Importer:2023-03-21